Pharmacokinetic–pharmacodynamic modelling for the determination of optimal dosing regimen of florfenicol in Nile tilapia (Oreochromis niloticus) at different water temperatures and antimicrobial susceptibility levels - Rairat, Tirawat; Hsieh, Chia‐Yu; Thongpiam, Wipavee; Chou, Chi‐Chung (Journal of fish diseases, 2019)
Optimized dosing regimen is key to the effective use of antibacterials and to minimizing drug‐related side effects. The current study established a pharmacokinetic–pharmacodynamic (PK‐PD) model for the determination of optimal antibacterial dosing regimen in fish taken into consideration the temperature‐dependent PK and the pathogen‐dependent antimicrobial susceptibility, using florfenicol (FF) in Nile tilapia as an example. The calculated optimal dosages significantly varied by temperature and target MIC levels, ranging from 2.23 (MIC 1 µg/ml at 24°C) to 34.88 mg kg−1 day−1 (MIC 4 µg/ml at 32°C). The appropriateness of the calculated dosages was successfully verified by the in vivo studies. After 5 days of oral administration of the calculated optimal dosage at 24°C, the predicted plasma drug values were in line with the mean observed Cmin(ss) while at 28 and 32°C underestimation of the Cmin(ss) in a dose‐dependent manner was observed and likely due to the occurrence of non‐linear PK at high dosages. The averaged serum protein binding of FF was 19.1%. Our results demonstrated the appropriateness and clinical applicability of the developed PK‐PD approach for the determination of optimal dosing regimens at given temperatures and MICs. Saturation metabolism and PK non‐linearity of FF in tilapia warrant further study.